2011
DOI: 10.1055/s-0031-1287668
|View full text |Cite
|
Sign up to set email alerts
|

Management of Abnormal Uterine Bleeding in Low- and High-Resource Settings: Consideration of Cultural Issues

Abstract: In non industrialized countries the incidence of heavy menstrual bleeding (HMB) appears to be similar to that of industrialized countries, although data is scanty. In low-resource settings, women with abnormal uterine bleeding (AUB) often delay seeking medical care because of cultural beliefs that a heavy red menstrual bleed is healthy. Efforts to modify cultural issues are being considered. A detailed history and a meticulous examination are the important foundations of a definitive diagnosis and management i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 78 publications
(117 reference statements)
0
15
0
1
Order By: Relevance
“…31,32 Some have suggested that there is a strong cultural component to this failure to recognize abnormal blood loss; some women believe that an ample flow of red blood indicates superior fertility or better cleansing. 39 Equally disturbing is the fact that even when women report years of excessive bleeding, they do not seek medical assistance for effective therapy; in our population more than two thirds reported more than 6 months of excessively heavy bleeding. Nearly 40% of women had previously required blood transfusion.…”
Section: Pcogs Papersmentioning
confidence: 63%
“…31,32 Some have suggested that there is a strong cultural component to this failure to recognize abnormal blood loss; some women believe that an ample flow of red blood indicates superior fertility or better cleansing. 39 Equally disturbing is the fact that even when women report years of excessive bleeding, they do not seek medical assistance for effective therapy; in our population more than two thirds reported more than 6 months of excessively heavy bleeding. Nearly 40% of women had previously required blood transfusion.…”
Section: Pcogs Papersmentioning
confidence: 63%
“…HMB is often associated with a complex of symptoms and the burden of the condition extends into many aspects of women's lives through the practical difficulties of excessive blood loss and having to curb normal social, cultural, and religious activities [15,16]. When neglected, HMB can lead to iron deficiency (with or without anemia) that results in chronic symptoms of fatigue, increased susceptibility to infections, and poor wound healing [17]. These symptoms may occur with iron deficiency on its own, even in the absence of anemia.…”
Section: Impact Of Heavy Menstrual Bleedingmentioning
confidence: 99%
“…In women with no underlying structural pathology, medical therapy is considered the preferred treatment for HMB [14]. However, in order to determine the efficacy of a new treatment, it is necessary to measure the actual physical monthly blood loss both prior to and during treatment.…”
Section: Introductionmentioning
confidence: 99%